THE DEDUCTIONS OF OPINIONS FROM ANALYZES OF POLITICAL TRENDS ON TWITTER - M.V.V.SUBRAHMANYA SARMADr. Deepak, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Assessment mining, often called thought research, has great potential for use in languageacquisition. The open-minded attitude toward anything or everyone can be traced using assumption mining